Insight into N-terminal localization and dynamics of engineered virus-like particles. Issue 64 (22nd October 2020) - Vervoort, Daan F. M.; Pretto, Chiara; van Hest, Jan C. M.
Abstract : The N-terminal localization and dynamic intermixing of engineered cowpea chlorotic mottle virus-like particles were studied independently from each other. Abstract : Virus-like particles composed of the cowpea chlorotic mottle virus (CCMV) capsid protein (CP) have been extensively studied as carrier systems in nanoscience. One well-established method to improve their stability under physiological conditions is to fuse a stimulus-responsive elastin-like polypeptide (ELP) to the N-terminus of the CPs. Even though the N-terminus should in principle be localized in the inner cavity of the protein cage, studies on the native CCMV revealed its accessibility on the particle surface. We verified that such phenomenon also applies to ELP-CCMVs, by exploiting the covalent functionalization of the CP N-terminal domain via a sortase A-mediated reaction. Western-blot analysis and Förster resonance energy transfer (FRET) experiments furthermore revealed this to be caused by both the external display of the N-termini and the interchange of CPs among preformed capsids. Our findings demonstrate the tunability of ELP-CCMV stability and dynamics and their potential effect on the exploitation of such protein cages as a drug delivery system.